Motown 50 [compact disc] : fanthology. (Motown Records, 2009)
As part of Motown's 50th anniversary celebration, the iconic label let fans have a say in creating the ultimate collection. From Diana Ross to Boyz II Men, there are tracks that span the label's storied history.